Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

For which of the following functions f is f(x) = f (1-x) for all x?

A. f (x) = 1 - x B. f (x) = 1 - x^2 C. f (x) = x^2 - (1 - x)^2 D. f (x) = x^2 (1 - x)^2 E. f (x) = x/(1 - x)

I've already seen quite a few GMAT questions of this type. They are quite easy to solve, since you understand the concept.

f(x)="some \ expression \ with \ variable \ x", means that the value of f(x) can be found by calculating the expression for the particular x.

For example: if f(x)=3x+2, what is the value of f(3)? Just plug 3 for x, f(3)=3*3+2=11, so if the function is f(x)=3x+2, then f(3)=11.

There are some functions for which f(x)=f(-x). For example: if we define f(x) as f(x)=3*x^2+2, the value of f(x) will be always positive and will give the following values: for x=-5, f(x)=3*(-5)^2+2=77; for x=0, f(0)=3*0^2+2=2. Please note that f(x) in this case is equal to f(-x), meaning that for positive values of x you'll get the same values of f(x) as for the negative values of x.

So, basically in original question we are told to define the expression, for which f(x)=f(1-x), which means that plugging x and 1-x in the expression must give same result.

A. f(x)=1-x --> 1-x is the expression for f(x), we want to find whether the expression for f(1-x) would be the same: plug 1-x --> f(1-x)=1-(1-x)=x. As 1-x and x are different, so f(x) does not equal to f(1-x).

The same with the other options:

(A) f(x)=1-x, so f(1-x)=1-(1-x)=x --> 1-x and x: no match.

(B) f(x)=1-x^2, so f(1-x)=1-(1-x)^2=1-1+2x-x^2=2x-x^2 --> 1-x^2 and 2x-x^2: no match.

(C) f(x)=x^2-(1-x)^2=x^2-1+2x+x^2=2x-1, so f(1-x)=2(1-x)-1=1-2x --> 2x-1 and 1-2x: no match.

(D) f(x)=x^2*(1-x)^2, so f(1-x)=(1-x)^2*(1-1+x)^2=(1-x)^2*x^2 --> x^2*(1-x)^2 and (1-x)^2*x^2. Bingo! if f(x)=x^2*(1-x)^2 then f(1-x) also equals to x^2*(1-x)^2.

Still let's check (E)

(E) f(x)=\frac{x}{1-x} --> f(1-x)=\frac{1-x}{1-1+x}=\frac{1-x}{x}. \frac{x}{1-x} and \frac{1-x}{x}: no match.

But this problem can be solved by simple number picking: plug in numbers.

As stem says that "following functions f is f(x) = f (1-x) for all x", so it should work for all choices of x.

Now let x be 2 (note that: -1, 0, and 1 generally are not good choices for number picking), then 1-x=1-2=-1. So we should check whether f(2)=f(-1).

(A) f(2)=1-x=1-2=-1 and f(-1)=1-(-1)=2 --> -1\neq{2};

(B) f(2)=1-x^2=1-4=-3 and f(-1)=1-1=0 --> -3\neq{0};

(C) f(2)=x^2-(1-x)^2=x^2-1+2x+x^2=2x-1=2*2-1=3 and f(-1)=2*(-1)-1=-3 --> 3\neq{-3};

(D) f(2)=x^2*(1-x)^2=(-2)^2*(-1)^2=4 and f(-1)=(-1)^2*2^2=4 --> 4=4, correct;

(E) f(2)=\frac{x}{1-x}=\frac{2}{1-2}=-2 and f(-1)=\frac{-1}{1-(-1)}=-\frac{1}{2} --> -2\neq{-\frac{1}{2}}.

It might happen that for some choices of x other options may be "correct" as well. If this happens, just pick some other number for x and check again these "correct" options only.

Re: Functions question [#permalink]
29 Dec 2010, 20:38

5

This post received KUDOS

Expert's post

1

This post was BOOKMARKED

metallicafan wrote:

Is there a faster way to solve this question rather than replacing each "x" by (1-x)? Thanks!

For which of the following functions f is f(x) = f(1-x) for all x?

A. f(x) = 1-x B. f(x) = 1-x^2 C. f(x) = x^2 - (1-x)^2 D. f(x) = (x^2)(1-x)^2 E. f(x) = x / (1-x)

Tip: Try to first focus on the options where terms are added/multiplied rather than subtracted/divided. They are more symmetrical and a substitution may not change the expression. I will intuitively check D first since it involves multiplication of the terms. _________________

Re: Please, someone explain [#permalink]
22 Jan 2012, 23:40

This one is quite simple. We have to substitute (1 - x) for x in each of the options and see which option yields the same result for both f(x) and f(1 - x).

However, careful observation of the options will easily tell you that only D will fulfill this condition because in D, the x now becomes (1 - x) and (1 - x) now becomes x. The overall outcome will remain the same. You don't even need to expand or do any calculations whatsoever. _________________

Re: Which of the following function.. [#permalink]
12 Oct 2012, 02:41

Expert's post

IanSolo wrote:

For which of the following functions f is f(x)=f(1-x) for all x ?

a. f(x)=1-x b. f(x)=1-x^2 c. f(x)=x^2 - (1-x)^2 d. f(x)=x^2(1-x)^2 e. f(x)=\frac{x}{1-x}

I find this question in gmat prep software, I have tried to solve it with picking number ( I have sostitute x with 1 and -1) but for all the answer the result was different from 1 and -1. How I can solve quickly this question? What is the level of this question?

Merging similar topics. Please ask if anything remains unclear.

Re: For which of the following questions is f(x)=f(1-x) for all [#permalink]
23 Mar 2013, 21:01

1

This post received KUDOS

You need to check for every option. Either you can replace x in every option with 1-x or you can take x = 1 and then check for which option f(1) = f(1-1) = f(0). In A f(1) = 1-1 = 0. f(0) = 1-0 = 1. In B f(1) = 1 - 1^2 = 0. f(0) = 1 - 0 = 1 In C f(1) = 1^2 - (1 - 1 )^2 = 1. f(0) = 0 - (1-0)^2 = 0 - 1 = -1 in D f(1) = 1(1-1)^2 = 0. f(0) = 0.(1-0)^2 = 0. ( Right answer ) And for option E you can take x = 2 because if you take x = 1 in denominator the denominator becomes zero, which makes the f(x) undefined. f(2) = 2/(1 - 2) = -2. f(1-2) = f(-1) = -1/(1-(-1)) = -1/2.

Re: For which of the following functions f is f(x)=f(1-x) for [#permalink]
26 Dec 2013, 00:21

Policarpa wrote:

Replacing x=4 and 1-x = -3 I get 16(9) - why is that wrong 4^2 (1-4)^2 = 16 (9), not at all f(4)

I'm sorry but I don't get your point. You mean if we plug in x = 4, the answer is incorrect? f(4) = 4^2*(1-4)^2 = 16*9 f(1-4) = (1-4)^2*[1-(1-4)]^2 = 9*16

D is correct. _________________

Please +1 KUDO if my post helps. Thank you.

"Designing cars consumes you; it has a hold on your spirit which is incredibly powerful. It's not something you can do part time, you have do it with all your heart and soul or you're going to get it wrong."